Wasting Democracy, Fueling Dissent: Refuse-Derived Fuels in Can Sant Joan (Catalonia) - Ruiz Cayuela, Sergio; Turhan, Ethemcan (Frontiers in Energy Research, 2019)
The cement industry is one of the most energy intensive in the world, contributing significantly to global greenhouse gas emissions. The use of refuse-derived fuels (RDF) in cement kilns is increasingly portrayed as a sustainable solution to reduce emissions while dealing with different types of waste. Nevertheless, the use of RDF in cement plants is contested by communities around the world, who are facing immediate environmental impacts. In this article, we examine the burgeoning movement against waste incineration in cement kilns legitimized as energy recovery. We start by revisiting the environmental justice literature, which laid the groundwork for the contemporary anti-RDF movement. Then, in order to highlight the energy dimension of RDF we focus on two energy-related concepts: energy justice and energy democracy. Through the case study of Can Sant Joan (Catalonia), we assess the suitability and usefulness of these concepts with the local movement against waste incineration. Our analysis suggests that the movement against RDF use can be further energized and strengthened by expanding into the realm of energy democracy. Both the anti-RDF and the energy democracy movement share a focus on the local scale, have similar typology of stakeholders involved, and favor a strong bottom-up approach while paying attention to unequal power relations. We also observe that these movements can mutually benefit from being better integrated with one another. Finally, we propose that a potential alliance between the Plataforma Antiincineració de Montcada i Reixac (PAMiR) and the Xarxa per la Sobirania Energètica (Xse) in Catalonia, can mobilize fruitful internal tensions toward a more inclusive and democratic future.